2021
DOI: 10.1038/s41396-021-00908-y
|View full text |Cite
|
Sign up to set email alerts
|

Predator-induced defence in a dinoflagellate generates benefits without direct costs

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 64 publications
0
21
2
Order By: Relevance
“…S3b). The presence of the (albeit variably) observed trade-off between growth and toxin production in response to copepod cues stands in contrast to a recent study which reported no cost to toxicity under varying levels of nitrogen limitation for the same strain of A. minutum (Ryderheim et al 2021). While these authors observed no reduction in growth rate, A. minutum cells shrank when exposed to copepodamides, an effect not seen in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…S3b). The presence of the (albeit variably) observed trade-off between growth and toxin production in response to copepod cues stands in contrast to a recent study which reported no cost to toxicity under varying levels of nitrogen limitation for the same strain of A. minutum (Ryderheim et al 2021). While these authors observed no reduction in growth rate, A. minutum cells shrank when exposed to copepodamides, an effect not seen in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…While these authors observed no reduction in growth rate, A. minutum cells shrank when exposed to copepodamides, an effect not seen in the current study. This discrepancy may be due to the higher cell densities and lower phosphate concentrations utilized (due to our use of K media) in the current study, compared to the study by Ryderheim and colleagues which used B1 media (Ryderheim et al 2021), which would be expected to intensify competition for a limiting resource (phosphate). The elevated competition in the current study explains the realized cost of toxin production in the form of reduced growth.…”
Section: Discussioncontrasting
confidence: 63%
“…Handling and selection of captured diatoms Feeding-current feeding copepods perceive particles that arrive in the feeding current individually as the particles come near the mechanoreceptory setae on the feeding appendages, which elicits a capture response (Koehl and Strickler 1981; Videos S1-S3). Copepods are known to be selective feeders, but prey selection appears to happen post capture while the prey is being handled by the feeding appendages, as demonstrated here for diatoms with different silica content, and elsewhere for dinoflagellates with different degrees of toxicity (Ryderheim et al 2021) or bioluminescence (Prevett et al 2019). The feeding appendages are equipped with both mechano-and chemosensors (Hallberg and Skog 2011) and both sensory modalities are probably involved in prey selection.…”
Section: Discussionmentioning
confidence: 65%
“…Theoretically there should be a cost associated with inducible defensive traits (Tollrian and Harvell, 1999), while defensive traits without costs are more likely to become constitutive (i.e., always present). However, some studies have been unable to establish costs of grazer induced traits in terms of reduced growth rate (Blossom et al, 2019;Ryderheim et al, 2021; but see Grønning and Kiørboe, 2020;Park and Dam, 2021). Our findings of reduced growth rate consequently suggests the presence of a direct allocation cost associated with expression of defensive traits, particularly in diatoms.…”
Section: Discussionmentioning
confidence: 58%